Performance Evaluation and Trait Association Analysis of Proso Millet Genotypes in Bajura District, Nepal - Bhatta, Kailash; Sipkhan, Pragati Raj; Bhusal, Bishnu; Khatri, Laxman; Dhakal, Rajendra (Agriculture Development Journal, 2025)
Proso millet (Panicum miliaceum L.), an indigenous crop cultivated by the farmers in Bajura for generations, was once the major millet crop of the area. The crop is now experiencing a sharp decline due to shifting food preferences, yield reduction and limited crop improvement program, which has threatened the existence of the crop in Nepal’s hill and mountains region. Therefore, an on-farm experiment was conducted using a randomized complete block design for the first time in Bajura, aimed at evaluating eight genotypes of proso millet—including two local landraces (Mal Chino and Dudhe Chino) and six accessions (NGRC07344, NGRC07345, NGRC07348, NGRC07349, NGRC07350, and NGRC07351) from the National Agriculture Genetic Resource Center (NAGRC)—under local conditions. The local landrace - Mal Chino outperformed all other genotypes yielding 2.06 t/ha and driven by maximum tillering (10.2), leaf number (69.73), and longest flag leaf (49.19 cm). Among the introduced lines, NGRC07345 recorded the second-highest yield (1.7 t/ha) and demonstrated adaptability in the studied region. Correlation and regression analysis identified flag leaf length and tiller number as a key determinant for grain yield. The study emphasized the potential of millets and landrace crops to improve food security and livelihoods in hilly and Himalayan areas of Nepal. Future efforts should be explored for multi-year and multi-location crop improvement study of promising and adapting genotypes to integrate in Nepal’s formal seed system.